Profile Matching, Seleksi Calon SISTEM PENUNJANG KEPUTUSAN PENERIMAAN KARYAWAN BARU PADA PT.QUADRANT SOLUTIONS DENGAN METODE PROFILE MATCHING - Hertyana, Hylenarti; Rahmawati, Eva; Mufida, Elly; Fachmi, Muhammad Fadillah (Jurnal Teknik Informatika UNIKA Santo Thomas, 2023)
Selection of prospective new employees is one of the methods used to obtain qualified employees and in accordance with the competence of expertise. The selection process to get suitable candidates has several criteria from the company. to assess the ability of prospective new employees objectively not subjectively and based on hunch. Assessment criteria are based on aspects of health, educational history, completeness of job application documents and also interviews. The method used in this research is Profile Matching. The concept of this method is to compare the individual abilities of prospective new employees to the ideal value of several aspects and factors. Implementation of the use of this method using the PHP programming language, MySQL database and website-based. The results of these recommendations can be used to assist in terms of decision making which are presented in the form of ratings or rankings. As well as being able to simplify the selection process and speed up the assessment process of candidate applicants who have already carried out a series of tests and interviews. It is hoped that the company can get candidates who are close to the value of the provisions that have been set. So that the decision support system using the profile matching method is considered appropriate to be used in assisting decision making.